Health Impacts of Pesticide Exposure Among Farmers: A Systematic Review and Implications for Agronursing Practice - Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Yeni Fitria; Emi Wuri Wuryaningsih; Robby Prihadi Aulia Erlando (KHD Production, 2026)
Pesticide exposure among farmers poses significant health risks globally; however, comprehensive recent evidence on the role of nursing in mitigating these hazards remains underexplored. This systematic review aims to synthesize empirical findings from 2024 to 2025 on the health impacts of pesticide exposure in farming populations and discusses implications for agronursing practice. Following the PRISMA 2020 guidelines, a systematic search was conducted across Scopus, PubMed, and ProQuest using the keywords